2017
DOI: 10.1523/jneurosci.3553-16.2017
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Excitability Brake Potassium Current IKDin Cold Allodynia Induced by Chronic Peripheral Nerve Injury

Abstract: Cold allodynia is a common symptom of neuropathic and inflammatory pain following peripheral nerve injury. The mechanisms underlying this disabling sensory alteration are not entirely understood. In primary somatosensory neurons, cold sensitivity is mainly determined by a functional counterbalance between cold-activated TRPM8 channels and Shaker-like Kv1.1-1.2 channels underlying the excitability brake current I Here we studied the role of I in damage-triggered painful hypersensitivity to innocuous cold. We fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 80 publications
2
54
1
Order By: Relevance
“…Thus, TASK-3 and HCN channels, though important for cold detection, are unlikely to mediate the differences in intrinsic excitability between these two populations. Future studies are needed to determine whether other potassium conductances, such as those mediated Kv1 Gonzalez et al, 2017a;Gonzalez et al, 2017b), contribute to differences in intrinsic excitability between menthol-sensitive andinsensitive DRG neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, TASK-3 and HCN channels, though important for cold detection, are unlikely to mediate the differences in intrinsic excitability between these two populations. Future studies are needed to determine whether other potassium conductances, such as those mediated Kv1 Gonzalez et al, 2017a;Gonzalez et al, 2017b), contribute to differences in intrinsic excitability between menthol-sensitive andinsensitive DRG neurons.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro experiments suggest that cold allodynia results from a shift in cellular activation thresholds such that neurons signalling extreme cold are now active at higher temperatures. 27 In contrast, oxaliplatin did not affect thermal activation thresholds of basal cold-sensing neurons in vivo, when the hindpaw was stimulated with a range of temperature drops delivered by a Peltiercontrolled thermode ( Figure 1E). 20 Moreover, when we quantified peak fluorescence intensity in response to cold as a surrogate for excitability before and after oxaliplatin, cold-evoked fluorescence intensity in both the basal and silent populations in the oxaliplatin group was no different to vehicle ( Figure 1F).…”
Section: Silent Cold-sensing Neurons Are Unmasked During Chemotherapymentioning
confidence: 90%
“…6 Conversely, cold-sensitive nociceptors that usually respond to extreme cold may become activated to milder temperature drops and consequently trigger cooling-evoked pain. 27,32 Finally, cold-insensitive nociceptors that provide noxious sensory input could acquire a de novo sensitivity to cooling. 10,23 Using in vivo imaging, we found that activation of normally silent, large-diameter coldsensing neurons is a common mechanism of cold allodynia in three clinically important, but etiologically-distinct, neuropathic pain states.…”
Section: Silent Cold-sensing Neurons In Cold Allodyniamentioning
confidence: 99%
See 1 more Smart Citation
“…Another possibility is that functional TRPM8 channels are required to provide information about temperature changes to enable warm perception. We addressed the likelihood of these two scenarios by acutely inactivating TRPM8 in the forepaw of wild type mice, using PBMC (1-Phenylethyl(2-aminoethyl)(4-benzyloxy)-3methoxybenzyl)carbamate), a selective antagonist of TRPM8 that has been shown to suppress cooling-responsive cells and to reduce cooling-evoked behavioural responses in mice (González et al, 2017;Knowlton et al, 2011;Yudin et al, 2016). We first trained wild type animals to report warming stimuli and, once mice were able to successfully report warming, we pharmacologically inactivated TRPM8 by performing a transdermal injection in the plantar side of the right forepaw and tested their warming perception ability ( Figure 7A,B).…”
Section: Pharmacological Inactivation Of Trpm8 Impairs Warming Percepmentioning
confidence: 99%